Geological and geodynamic characteristics in relation to the earthquake of June 23, 2001 - Jacay, Javier (2004)
The manifestations of external geodynamics that have happened in relation to the earthquake of June 23, 2001, in the Andean high provinces of the departments of Tacna and Moquegua are presented here. In the Moquegua and Tacna urban center areas, provinces of Mariscal Sánchez Cerro (Puquina, La Capilla and Omate) as well as in Locumba and Tarata, the infrastructure that has been affected, is due more to deficiencies in construction and/or because of local physical characteristics of the ground and underground. It is concluded that the manifestations of external geodynamics of a wider span are located between the Highlands West border and the Incapuquio Faults system, having this strip acted like a probable resilience zone to the seismic waves.